PENGGUNAAN BAHASA GAUL TERHADAP EKSISTENSI BAHASA INDONESIA PADA MASYARAKAT - Yenni Febiola Febrianti (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
This research was conducted because of the widespread use of slang among the Indonesian population, especially in the Community of Kelurahan Medan Tenggara. This study aims to: 1) find out the use of slang in the people of Medan Tenggara Village, and 2) find out the problems regarding the factors that influence the use of slang on the existence of Indonesian in the residents of Medan Tenggara Village. The method used is descriptive qualitative. Data collection techniques in the form of field research. Respondents in this study were the Community of Kelurahan Medan Tenggara with a total of 15 people. The results showed: 1) slang among the people of Medan Tenggara Village is something that is commonly used in daily communication either with peers or with the environment, and 2) the influence of the use of slang in the people of Medan Tenggara Village has an effect on the existence of Indonesian, As a result, people do not know the standard language, and people do not understand the use of proper spelling.